Cerebral Proliferative Angiopathy: Case Report - Gatto, Luana Antunes Maranha; Brisson, Rodrigo Tavares; Demartini, Zeferino, Jr; Koppe, Gelson; Rocha, Carlos, Jr (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Proliferative angiopathy (PA) is a rare cerebral vascular disease in which anomalous vessels continually recruit additional feeder arteries, amid a functional brain parenchyma. We report the case of a young woman with progressive history of headache, motor deficit, seizures and drowsiness. She received a misdiagnosis of brain arteriovenous malformation (AVM) and evolved with dysarthria and cognitive decline after an unsuccessful embolization performed at another institution. We opted for conservative treatment with periodic control by imaging tests. Proliferative angiopathy differs in natural history, prognosis, histopathology and treatment of the usual AVMs. Endovascular procedures aggravate the neurological deficits, which are usually progressive and tend to worsen over time.
Keywords: intracranial arteriovenous malformations; central nervous system vascular malformations; therapeutic embolization; endovascular procedures